DEVELOPING INQUIRY LEARNING MODEL-BASED ENGLISH INSTRUCTIONAL MATERIALS FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Putri Nurul Ifani; Sitti Nurpahmi; Djuwairiah Ahmad (ELTIES : English Language Teaching for EFL Learners, 2020)
This research aimed at developing instructional English materials for the students of the seventh grade especially in basic competencies 3.4 and 4.4 at  MTs  Madani  Pao-pao  based  on  2013  curriculum  supported  by  using  inquiry  learning  model  and  using  the concept of HOTS. The research design is Research and Development (R&D )with the combination of   ADDIE   model. The  procedures  included  analyzing  materials   needed   by spreading  questionnaire  to  the  students  and  analyzing  the  basic   competencies, designing a  blueprint  of  materials and the instructional materials, and validating the material by the expert. There were 146 students as the respondents, teachers, and experts. The instruments used in this research were the documents, questionnaires, and validation checklist. There were three systematic  aspects : materials  Systematic  Organization,  Systematic  English   Teaching  and  Systematic  Content  of  English.  Therefore,  the  result  indicated  that  based on experts judgment,  the  developed basic competency  3.4  and 4.4 were applicable to be taught at the seventh grade students  of  Junior  High  School.